Analisis Strategi Pemasaran dalam Upaya Meningkatkan Penjualan pada Usaha Kripik Tempe Mekar Sari di Trenggalek - Nikmah, Siti Nurkamilatun; Hastuti, Maria Agatha Sri Widyanti (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
In supporting the marketing plan, the company must first prepare a marketing strategy so that the industry can find out the market conditions first and see the position of its company in the market. The type of research used is descriptive research with a qualitative approach. Data was collected through observation, interviews, and documentation. This study aims to disseminate the marketing strategy implemented by the Mekar Sari tempeh chips business in Trenggalek in an effort to increase its sales. The results of this study indicate that the marketing strategies used include product diversification, competitive pricing, and promotion through social media and participation in local exhibitions. However, the use of digital marketing is still not optimal. The main obstacles faced by this MSME are tight competition, fluctuations in raw material prices, and limited distribution. It is recommended that this business optimize the use of digital platforms to expand market reach and increase sales volume.